Kinetic study of the effect of sub-atmospheric conditions on the laminar burning velocity of high C2H6 content natural gas mixtures - Yepes, Hernando Alexander; Vargas, Arley Cardona; Arrieta, Andrés Amell (Combustion theory and modelling, 2022)
The laminar burning velocity (S L ) was measured at sub-atmospheric pressure (0.84 atm) and an environmental temperature of 295 ± 2 K for two high C 2 H 6 content fuel mixtures, 75% CH 4 - 25% C 2 H 6 (mixture M1), and 50% CH 4 - 50% C 2 H 6 (mixture M2), as well as the pure constituent fuels. The equivalence ratios for the experiments ranged between 0.8 and 1.4. Numerical calculations predicting S L were performed using 3 detailed reaction mechanisms, finding GRI-Mech 3.0 to achieve the best agreement at the pressure conditions evaluated. The pre-exponential factor of reaction H + O 2 = O + OH (R38) was modified in order to improve the numerical results at sub-atmospheric conditions. Kinetic analysis by means of the defined reaction factor ( ) was carried out to identify the mechanism for S L changes at sub-atmospheric conditions. According to the experimental results, S L increased by 15.9% and 26.3% for mixtures M1 and M2, respectively, at 0.84 atm as compared to 1.0 atm. The reaction pathways elaborated employing F R indicate that the increase in S L at sub-atmospheric conditions is caused by increased CH 3 radical production by reaction C 2 H 5 + H = 2CH 3 (R159), which increases the formation of H radical through reactions O + CH 3 = H + CH 2 O (R10) and O + CH 3 = H + H 2 + CO (R284). The recombination reactions associated with the production of CH 4 and C 2 H 6 also contribute to S L increases at sub-atmospheric conditions.